Strength and Ductility of RC Columns Retrofitted by FRP under Cyclic Loading - Tavio Tavio; Karmila Achmad; Parmo Parmo; Agus Sulistiawan (IPTEK Journal of Proceedings Series, 2014)
Rapid increasing of population and limited city area as well as better awareness on the green open area of the city, which is ideally about 30 percent, have forced the development of the buildings vertically. The increasing number of high-rise buildings and skyscrapers are the evidence that the development of the buildings in the cities of Indonesia are heading towards the over-ground space. However, the vertical development is known to be highly vulnerable to earthquake hazard. The revised Indonesian seismic map has increased the seismic load in most of the seismic zones in Indonesia. To create a safe and healthy city, a comprehensive urban planning and design is required. A good urban planning and code-based design must also be adopted to assure a safe building structure for the dwellers. This study is intended to observe the possibility of using alternative materials to improve the performance of the existing buildings which have not followed the existing earthquake-resistant building code through the implementation of Fiber Reinforced Polymer (FRP) wrap on structural members. The strength and ductility enhancements of the columns retrofitted with external confinement using FRP are found when compared with the unconfined control column. The results indicated that the maximum loads of each confined columns have increased by 33.52, 54.97, 36.61, and 40.73 percent, respectively, for columns C-1G, C-1C, C-1RC, and C-1RG. The ductility of columns C-1C and C-1G have increased by 122.73 and 53.30 percent, but decreased by 15.24 and 66.31 for columns C-1RG and C-1RC when compared with the unconfined control column C-1, respectively. This is due to the unintended premature failure at the upper end of the column C-1G and an indication that the secondary fiber direction which was placed vertically has contributed to the longitudinal steel of C-1RC in increasing its capacity.